Chemical composition of Rhodocyclus gelatinosus biomass produced in poultry slaughterhouse wastewater - Ponsano,Elisa Helena Giglio (2003)
Rhodocyclus gelatinosus R1 grew photoautotrophically in poultry slaughterhouse wastewater inside glass columns (90x670 mm) during 7 days at 31 ± 4ºC, under anaerobiosis and lightness supplied by daylight plus 3 (100W) incandescent and 4 (40W) fluorescent lamps. The culture was centrifuged (4,500xg/20 min) and lyophilized to originate a bacterial biomass with 7.1% moisture content. Chemical composition investigation showed 67.6% crude protein, 27.6% total carbohydrate, 0.6% lipids and 4.2% ash (dry weight). Amino acid composition of the biomass was similar to others described in the literature for Rhodocyclus gelatinosus and for other photosynthetic bacteria. Effluent COD removal after cultivation and elimination of the biomass was around 90%. The valuable chemical composition of Rhodocyclus gelatinosus R1 biomass and the high content in essential amino acids signs for the potential use of the product in poultry feed.